Fine particulate matter (PM2.5, PM10): A silent catalyst for chronic lung diseases in India; a comprehensive review - Deepak Chandra Joshi; Pooja Negi; Suprabha Devi; Himanshu Lohani; Rohit Kumar; Madhu Gupta; Long Chiau Ming (Environmental Challenges, 2025)
This review assesses the role of microparticles (PM2.5 and PM10) as a silent yet pivotal cause of chronic lung disease in India. It explores these pollutants' sources, composition, and health effects while providing an overview of regulations, public health consequences, and areas requiring further research. A critical appraisal of validated sources, including government reports, peer-reviewed literature, and environmental databases, was conducted, focusing on the past five years of PM levels in Indian cities and their association with chronic lung disease. The study investigates pathways of lung injury through oxidative stress, inflammation, and sustained respiratory impairment. Findings reveal that PM2.5 and PM10 levels in both urban and rural areas frequently exceed WHO guidelines, particularly in major cities, contributing to increased cases of COPD, asthma, lung cancer, and pulmonary fibrosis. The most vulnerable groups, including children and the elderly, bear a disproportionately high disease burden. Furthermore, PM pollution places a significant strain on India's healthcare system due to rising treatment costs and diminished quality of life. As particulate matter remains a critical public health issue affecting respiratory health and healthcare resources, urgent policy interventions, technological advancements, and grassroots initiatives are necessary to mitigate its impact. Additional scientific research is needed to bridge gaps in understanding PM's long-term health effects and develop advanced monitoring systems for better air quality management.